The divisive state of social policy : the 'Bedroom Tax', austerity and housing insecurity. - Bogue, Kelly (Policy Press, 2019)
Few aspects of austerity politics have been as divisive as the 'Bedroom Tax'. This book provides a vivid and authoritative assessment of the impact of social housing reform on tenants and society, using personal stories from one estate to explore its connections to issues including housing insecurity, poverty and damage to social networks.